Viability of Haemonchus placei parasitism in experimentally infected young goats - dos Santos, Isabella Barbosa [UNESP]; Giquelin Maciel, Willian [UNESP]; Felippelli, Gustavo [UNESP]; Barbosa Toscano, João Henrique [UNESP]; Cayeiro Cruz, Breno [UNESP]; De Souza Chagas, Ana Carolina [UNESP]; Soares, Vando Edésio [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; da Costa, Alvimar José [UNESP]; de Oliveira, Gilson Pereira [UNESP] (Elsevier, 2019)
The present study aimed to evaluate the viability of Haemonchus placei parasitism in experimentally infected goats. For that, 14 75 days old kids male Saanen kids were placed in one of the four experimental groups: GI – infected with 5000 H. placei L3 (n = 4); GII – infected with 5000 H. contortus L3 (n = 4); GIII – infected with 2500 H. contortus L3 + 2500 H. placei L3 (n = 4), and GIV – control, inoculated with distilled water (n = 2). Each kid received, orally, the infective dose in a single inoculum. Based on daily fecal egg counts, the average pre-patent period was determined as 24 days for H. contortus, and 31 days for H. placei. Regarding the Haemonchus spp. recovered at necropsy, the experimental groups GI, GII, and GIII had, respectively, an average of 25.5, 619.5, and 724.75 (120 H. placei, and 604.75 H. contortus) adult specimens, and no immature forms. Under the conditions of this study, the viability of goat infection by H. placei was confirmed, although, with low susceptibility. Nevertheless, the parasitism of this helminth species was more intense when associated with H. contortus. This fact indicates that in common grazing between cattle and young goats, when the latter end up ingesting both Haemonhcus species, especially in a mixed infection, H. placei may also parasitize them.
Keywords: Goat breeding; H. placei; Haemoncosis; Small ruminants